2009
DOI: 10.1002/jmri.21983
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic systemic fibrosis in liver disease: A systematic review

Abstract: Nephrogenic systemic fibrosis (NSF) may develop in patients with liver disease, a fact highlighted by Food and Drug Administration (FDA) announcements cautioning against the use of gadolinium‐based contrast agents (GBCAs) in select liver disease patients. The purpose of this systematic literature review is to characterize the risk of NSF in patients with liver disease. All published articles on NSF from September 2000 through August 2008, were identified via PubMed searches and examination of articles' referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 111 publications
2
26
0
Order By: Relevance
“…1,2 Eflornithine, the only prescription topical agent approved in the United States for female facial hirsutism, has only a 32% success rate and has not been evaluated in men. 1 Therefore, additional topical treatments effective in preventing hair growth are needed. The antiviral agent cidofovir has been reported to induce local alopecia when applied topically.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Eflornithine, the only prescription topical agent approved in the United States for female facial hirsutism, has only a 32% success rate and has not been evaluated in men. 1 Therefore, additional topical treatments effective in preventing hair growth are needed. The antiviral agent cidofovir has been reported to induce local alopecia when applied topically.…”
Section: Methodsmentioning
confidence: 99%
“…Many risk factors have been implicated, including liver disease, 1 erythropoietin, 2 proinflammatory and hypercoagulable conditions, dialysis, and gadolinium exposure. 3 Diabetes mellitus (DM) and renal failure are both associated with fibrosing disorders.…”
mentioning
confidence: 99%
“…A review of 335 NSF cases in 2009 confirmed liver disease in 41 patients but failed to demonstrate any statistically significant increased risk due to the liver disease alone. Renal impairment was severe in all cases bar one, in which AKI was described [24]. The conclusion drawn in the European and American guidelines is that patients most at risk of NSF are those with CKD stage 4 or 5, including those needing dialysis and those with reduced renal function who have or are awaiting liver transplantation.…”
Section: Nsf Risk: Renal Impairment and Liver Diseasementioning
confidence: 98%
“…Erythropoietin use was seen in up to 80 %, although this may simply have reflected erythropoietin resistance relating to chronic inflammation [23]. Other risk factors, including liver disease [24], immunosuppression [25], hyperphosphatemia [26], and acidosis [2], were reported but not consistently reproduced. At this stage, it appeared that NSF involved a process of sensitizing events (renal disease and some proinflammatory condition) and an unidentified trigger (e.g., allergen deposition) [27].…”
Section: Evidence For a Link With Gadolinium-based Contrast Agentsmentioning
confidence: 99%
“…We present current guidelines for injection of GBCA as used in the United States, Canada, Europe (20) and Japan (21). Furthermore, risk factors for NSF are reviewed (22), and NSF is discussed in the context of renovascular (23) and liver disease (24). The issue of relative risk of NSF versus CIN is addressed in the excellent review by Martin and other experts on this topic (25).…”
Section: Open Questionsmentioning
confidence: 99%